Detection of subsurface archaeological features using the GPR method with a 250 MHz antenna in Borsippa site, Babylon, Iraq - Kareem, Hamza A.; Abd, Najah A. (Iraqi Journal of Science, 2024)
The GPR method was used to determine the depth and extent of the subsurface archaeological features at the archaeological site of Borsippa. The extensions of the archaeological walls were identified through the creation of three-dimensional maps. The LMX200 device conducted the survey using a 250 MHZ antenna. sixty parallel profiles were collected and processed by GPR Slice software. Several reflections of possible archaeological walls buried at different depths and extensions of 2, 4, 6, 11, and 20 m were identified. The 250 MHz antenna gave clear reflections of the archaeological walls, with a penetration depth of up to 4 meters. The time slice map identified a buried archaeological structure at 1–1.1 m deep, consisting of many rooms with thick walls up to 2-3 m.